Postfordizem in nemška kakovost - Stanojević, Miroslav (Teorija in praksa, 1999)
The key features of diversified quality production on the one side, and the features of the contemporaneous Fordist production system, on the other, reveals that extraordinary success of the diversified quality production wasinduced by its Fordist environment. As Fordist mass production was primarily driven by price competition, it left demand for quality goods uncovered. These historically specific market constellations enabled forming a German model of diversified quality production. Being specialised for quality production within the Fordist context, German system of diversified quality production is facing problems in the post-Fordist environment, where the new flexible production systems narrow, fragment and destabilise traditional German markets.
Keywords: economics; ekonomija; proizvodni sistemi; fordizem; proizvodnja; kvaliteta; politična ekonomija; postfordizem